2015
DOI: 10.1017/s136898001500230x
|View full text |Cite
|
Sign up to set email alerts
|

Are 24 h urinary sodium excretion and sodium:potassium independently associated with obesity in Chinese adults?

Abstract: Objective: To examine the association of 24 h urinary Na excretion and Na:K with obesity in Chinese adults. Design: Population-based cross-sectional study using a four-stage stratified sampling strategy. Setting: Shandong Province, China. Subjects: Chinese adults (n 1906) aged 18-69 years who provided complete 24 h urine samples. Results: Odds of obesity increased significantly across increasing quartiles of urinary Na excretion (1·00, 1·54, 1·69 and 2·52, respectively, for overweight; 1·00, 1·20, 1·50, and 2·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Additionally, one study performed by Jain et al [ 21 ] in USA showed that the patients with the highest potassium intake relative to sodium had the lowest risk of obesity, and this effect was most pronounced for African American subjects. Ge et al [ 22 ] study revealed that urinary sodium-to-potassium ratio was also associated with obesity independently, and high sodium-to-potassium ratio could increase the risk of obesity, which was similar to the results of Jain et al .…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Additionally, one study performed by Jain et al [ 21 ] in USA showed that the patients with the highest potassium intake relative to sodium had the lowest risk of obesity, and this effect was most pronounced for African American subjects. Ge et al [ 22 ] study revealed that urinary sodium-to-potassium ratio was also associated with obesity independently, and high sodium-to-potassium ratio could increase the risk of obesity, which was similar to the results of Jain et al .…”
Section: Resultssupporting
confidence: 74%
“…After removing duplicates and screening of titles and abstracts, we identified 82 studies for full-text assessment. Based on our inclusion criteria and exclusion criteria, 8 studies [ 10 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] (7 cross-sectional studies and 1 cohort study) were included in the systematic review and meta-analysis, as shown in Figure 1 . There were 51,702 participants from four different countries (3 studies from China, 2 studies from Japan, 2 studies from Korea and 1 study from USA), consisting of 15,527 obesity cases and 10,482 MetS cases.…”
Section: Resultsmentioning
confidence: 99%
“…High salt intake has been widely reported to be associated with elevated blood pressure (BP) (1-3) and increased risk of cardiovascular diseases (4,5). Over the last few years, several studies have reported that dietary salt intake was associated with overweight/obesity and put forward a hypothesis that salt intake may be an independent risk factor for overweight/obesity in adults (6)(7)(8)(9)(10)(11)(12)(13), but results from previous studies are controversial (14,15). Previous studies have limitations such as use of a single spot urine (15) or dietary recall (6,12,14) to estimate daily salt intake, which have been criticized for large bias in estimating individual salt intake (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increased consumption of processed calorie-dense foods may result in excessive sodium intake, thus energy intake may be important for the relation between salt intake and overweight/obesity. Unfortunately, lack of data on energy intake has weakened the meaning of data from some previous studies (7,10). Only a few studies in adults used 24h urine collection to estimate salt intake with adjustment for energy intake in multivariable models and found that the relation between salt intake and obesity may be independent from energy intake (8,9,11,13).…”
Section: Introductionmentioning
confidence: 99%
“…We excluded 24‐hour urine collection with a small volume, which was validated less than 500 mL per day and collection intervals that were not within 24 hours . Furthermore, the most important exclusion criterion was creatinine excretion, which has already been proved to be an effective standard and been used widely in many previous studies . This study also had some limitations.…”
Section: Discussionmentioning
confidence: 99%